The Effect of Tiktok Video On Vocabulary Mastery of Eight Grade Student at SMP Negeri 2 Siantar - Sidabutar, Yohana Anggita; Napitupulu, Selviana; Hutabarat, Novra Melisa P (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
The researcher incorporated TikTok videos into a study aimed at evaluating their impact on eighth-grade students' vocabulary mastery at SMP Negeri 2 Siantar during the 2024/2025 academic year. This study utilized a quasi-experimental design with a quantitative approach, involving two groups: an experimental class and a control class. The experimental class consisted of students from VIII-1, while the control class comprised students from VIII-2, selected through purposive sampling. To analyze the data, the researcher applied the t-test formula to assess the effect of TikTok on vocabulary mastery. The analysis revealed the mean scores for both pre-tests and post-tests in the experimental and control classes. Specifically, the experimental class had a pre-test mean score of 31.61 and a post-test mean score of 72.90, whereas the control class recorded pre-test and post-test mean scores of 34.52 and 66.61, respectively. The standard deviation for the experimental class was 10.549, and for the control class, it was 11.575. The t-test results showed a significance value (Sig) of 0.000. Based on these findings, the researcher concluded that the alternative hypothesis (Ha) is accepted, while the null hypothesis (H0) is rejected. Therefore, it can be inferred that TikTok has a significant effect on enhancing students' vocabulary mastery, particularly among seventh graders.